2008
DOI: 10.1021/jp8010537
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Time-Resolved Energy-Dispersive XAFS Study on Photodeposition of Rh Particles on a TiO2 Photocatalyst

Abstract: It is the first report to observe the real-time behavior of photodeposition and the continuous structural change of Rh metal particles anchored on a TiO2 photocatalyst from an aqueous solution of Rh trivalent ions in the liquidsolid suspension by an in situ time-resolved energy-dispersive X-ray absorption fine structure (DXAFS) analysis. The DXAFS analysis uncovered that the Rh trivalent ions are adsorbed on the surface of the TiO2 photocatalyst, followed by reducing to the Rh metal particles by acceptance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 36 publications
(49 reference statements)
0
37
1
Order By: Relevance
“…7a. Based on previous studies, the first shell peak at 2.76 Å in the Rh-only data can be assigned to the Rh-Rh bond [14,[38][39][40]. With the addition of Fe, this peak begins to broaden and eventually splits into two distinct peaks at 2.53 Å and 2.79 Å at the highest Fe loading.…”
Section: Catalyst Structure Under Reaction Conditions: In Situ Xrd Anmentioning
confidence: 79%
“…7a. Based on previous studies, the first shell peak at 2.76 Å in the Rh-only data can be assigned to the Rh-Rh bond [14,[38][39][40]. With the addition of Fe, this peak begins to broaden and eventually splits into two distinct peaks at 2.53 Å and 2.79 Å at the highest Fe loading.…”
Section: Catalyst Structure Under Reaction Conditions: In Situ Xrd Anmentioning
confidence: 79%
“…In the absence of an electrochemical setting, this oxidation process must take place on the same photocatalyst in which reductive deposition of the metal is occurring. Research from several groups [233,555,1113,1118,1124,1132,1135,1136,1138,[1149][1150][1151]1156,1158] has shown that choice of the sacrificial electron donor (usually an organic) is key to efficient metal photoreduction. This is not simply an issue of balancing redox potentials (although that is important), but also selecting an electron donor that does not compete for surface sites or otherwise interfere with the metal reduction process.…”
Section: Photoreduction Reactantsmentioning
confidence: 99%
“…Of these, quick X-ray absorption fine-structure (XAFS) spectroscopy is one of the most useful methods to observe AuNP formation process in situ because the chemical state and the structure of AuNP can be analyzed from the spectra. [15,16,17] Recently, Polte et al observed the formation process of AuNPs with citric acid by coupled in situ XANES and small-angle X-ray scattering (SAXS) spectroscopy. [18] This helped to describe the mechanism of nanoparticle formation, which was found to comprise different steps of particle growth via both the coalescence of nuclei and further monomer attachment.…”
Section: Junya Ohyamamentioning
confidence: 99%